Fluid-structure-sound interactions and control : proceedings of the 4th Symposium on Fluid-Structure-Sound Interactions and Control /: proceedings of the 4th Symposium on Fluid-Structure-Sound Interactions and Control. (©2019) - Unknown
No abstract available